ANALISIS PENGARUH DURASI JAM BELAJAR TERHADAP MOTIVASI BELAJAR SISWA DI SMKN 1 METRO - Ageng Sinta Pratiwi; Andri Saputra; Eko Prihandono; Partono; Husnul Khotimah; Fransiskus Andi Juan (JURNAL FIRNAS, 2024)
Abstract: The current challenges in national education persist, and they remainunsolvable as the content transformed during the education and learning processconstantly faces the pressures of advancements in science, technology, andsocietal progress. The demands of an independent curriculum are a fundamentalurgency in the world of education that emphasizes aspects of development and21st century skills, in its implementation in vocational high schools groupingsubjects becomes one form of implementation of these aspects by combiningscience and social studies subjects into IPAS in the form of projects, it makes theduration of learning hours long which will certainly affect student interest andmotivation during the learning process, based on observations at SMKN 1 Metrothat the use of the duration of learning hours is fairly ineffective because itrequires 7 hours of IPAS learning in one meeting session.